Pengembangan Tari Lamang Di Sanggar Bidodari Kanagarian Koto Gadang Guguak Kabupaten Solok - Mica Parmita; Darmawati Darmawati (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to reveal, describe and analyze about the Development of Lamang Dance at the Bidodari Kanagarian Studio Koto Gadang guguak Solok Regency. This type of research is descriptive analysis method research. Object of research This is the Lamang dance at the Bidodari Kanagarian Studio Koto Gadang Guguak Regency Solo. The types of data in this research are primary and secondary data. Research instrument this is the researcher himself. Data collection techniques are carried out by means of literature, observation, interviews and documentation. The data collected was analyzed using techniques interpretation so that the truth can be obtained. The results of the research show that the Lamang Dance in Nagari Koto Gadang Guguak has experienced development that can be seen in terms of quality and quantity. On in terms of quality, namely from the aspects of movement, floor patterns and costumes. In terms of quantity, namely from the aspect of increasing the number of actors from 2 female dancers to 8 dancers Woman. Costumes developed in terms of colors, headdresses and clothing. So the process of developing the Lamang dance in Nagari Koto Gadang Guguak was because there was a desire Meri Suryati is the younger sister of the founder and permanent supervisor of Sanggar Bidodari maintain the Lamang dance by changing it to an attractive Lamang dance used by the people of Nagari Koto Gadang Guguak.